The N-end rule in Escherichia coli: cloning and analysis of the leucyl, phenylalanyl-tRNA-protein transferase gene aat. - Shrader, T E (1993)
The N-end rule relates the in vivo half-life of a protein to the identity of its N-terminal residue. Distinct versions of the N-end rule operate in bacteria, fungi, and mammals. We report the cloning and analysis of aat, the Escherichia coli gene that encodes leucyl, phenylalanyl-tRNA-protein transferase (L/F-transferase), a component of the bacterial N-end rule pathway. L/F-transferase is required for the degradation of N-end rule substrates bearing an N-terminal arginine or lysine. The aat gene maps to the 19-min region of the E. coli chromosome and encodes a 234-residue protein whose sequence lacks significant similarities to sequences in data bases. In vitro, L/F-transferase catalyzes the posttranslational conjugation of leucine or phenylalanine to the N termini of proteins that bear an N-terminal arginine or lysine. However, the isolation and sequence analysis of a beta-galactosidase variant engineered to expose an N-terminal arginine in vivo revealed the conjugation of leucine but not of phenylalanine to the N terminus of the beta-galactosidase variant. Thus, the specificity of L/F-transferase in vivo may be greater than that in vitro. The aat gene is located approximately 1 kb from clpA, which encodes a subunit of ATP-dependent protease Clp. Although both aat and clpA are required for the degradation of certain N-end rule substrates, their nearly adjacent genes are convergently transcribed. The aat gene lies downstream of an open reading frame that encodes a homolog of the mammalian multidrug resistance P glycoproteins.